Analysis of Students' Mathematical Critical Thinking Ability on Polyhedron in Term of Learning Styles - Hasenda Alfa Dinara; Fadhilah Rahmawati; Aprilia Chasanah (Universitas Sarjanawiyata Tamansiswa, 2022)
This research aims to describe the critical thinking ability of mathematics students of class VIII of Junior High School N 2 Magelang. The subjects in the study were students of grades VIII-A and VIII-D. The research was carried out in the even semester of the 2021/2022 school year. The data collected is in the form of learning style questionnaire results, mathematical critical thinking ability tests, and interviews in an unscathodox manner. Learning style questionnaires are used to determine students' learning styles, tests to measure mathematical critical thinking ability consist of four questions about the description of polyhedron materials. The results of the questionnaire and test were then analyzed according to the indicators of mathematical critical thinking ability used in this study, namely providing basic clarification, bases for a decision, inference, advanced clarification, supposition and integration. The results of data analysis show that students' critical thinking ability in visual, auditorial, and kinesthetic learning styles is classified as moderate. The results of this study can provide information to teachers about students' critical thinking ability so that teachers are expected to be able to design learning activities that can improve students' critical thinking skills to be good.